Is Being Argentinean Being Far Away? Julio Cortázar’s Sides and Futures (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2024)
In the 1970s, Cortázar underwent a series of ideological and aesthetical transformations, following his participation in the Latin American emancipation movements, but also in the context of a general world paradigm shift. Writing and conceptualizing his Latin Americanism from France, where he was living, Cortázar's work offers us interesting ways to understand a changing world. In turn, this approach offers us an equally suggestive way to rethink Cortázar. This article examines critically several of these mirroring aspects and effects.